Tort Law Dalam Konteks Hukum Perdata: Penegakan Hak Korban Kerugian - Putri Handayani; Adeline Pastika Muham; Rahmat Fitra; Sri Hadiningrum (Jurnal Relasi Publik, 2024)
In the context of civil law, Tort Law plays an important role in upholding the rights of loss victims. Tort law is rooted in the principle that every individual has the right to live without experiencing interference from the unlawful acts of others. The aim of this research is to find out how Tort Law works in the context of Civil Law: Enforcement of the Rights of Loss Victims. The method used in this research is qualitative research in the nature of library research which uses books and other literature as the main object. Data analysis in this research looks for sources of information regarding tort law in the context of civil law: Enforcement of the Rights of Loss Victims. Based on research results, Tort Law in the context of civil law discusses violations of civil law that cause harm to individuals or property. The principle is to provide compensation to victims who suffer as a result of unlawful actions.